Effects of metformin on inflammation, oxidative stress, and bone loss in a rat model of periodontitis - Araújo, Aurigena Antunes de (2017)
Aim To evaluate the effects of metformin (Met) on inflammation, oxidative stress, and bone loss in a rat model of ligature-induced periodontitis. Materials & methods Male albino Wistar rats were divided randomly into five groups of twenty-one rats each, and given the following treatments for 10 days: (1) no ligature + water, (2) ligature + water, (3) ligature + 50 mg/kg Met, (4) ligature + 100 mg/kg Met, and (5) ligature + 200 mg/kg Met. Water or Met was administered orally. Maxillae were fixed and scanned using Micro-computed Tomography (μCT) to quantitate linear and bone volume/tissue volume (BV/TV) volumetric bone loss. Histopathological characteristics were assessed through immunohistochemical staining for MMP-9, COX-2, the RANKL/RANK/OPG pathway, SOD-1, and GPx-1. Additionally, confocal microscopy was used to analyze osteocalcin fluorescence. UV-VIS analysis was used to examine the levels of malondialdehyde, glutathione, IL-1β and TNF-α from gingival tissues. Quantitative RT-PCR reaction was used to gene expression of AMPK, NF-κB (p65), and Hmgb1 from gingival tissues. Significance among groups were analysed using a one-way ANOVA. A p-value of p<0.05 indicated a significant difference. Results Treatment with 50 mg/kg Met significantly reduced concentrations of malondialdehyde, IL-1β, and TNF-α (p < 0.05). Additionally, weak staining was observed for COX-2, MMP-9, RANK, RANKL, SOD-1, and GPx-1 after 50 mg/kg Met. OPG and Osteocalcin showed strong staining in the same group. Radiographically, linear measurements showed a statistically significant reduction in bone loss after 50 mg/kg Met compared to the ligature and Met 200 mg/kg groups. The same pattern was observed volumetrically in BV/TV and decreased osteoclast number (p<0.05). RT-PCR showed increased AMPK expression and decreased expression of NF-κB (p65) and HMGB1 after 50 mg/kg Met. Conclusions Metformin, at a concentration of 50 mg/kg, decreases the inflammatory response, oxidative stress and bone loss in ligature-induced periodontitis in rats.